Cost analysis and cost-effectiveness of traditional Chinese medicine in lung cancer: a scoping review - An, Ran; Su, Gangqiang (Frontiers in Public Health, 2025)
BackgroundLung cancer remains the leading cause of cancer mortality worldwide, with non-small cell lung cancer (NSCLC) comprising the majority of cases. Traditional Chinese Medicine (TCM) has been increasingly integrated into lung cancer care, particularly in East Asia, but its economic impact remains unclear.MethodsA scoping review was conducted to synthesize evidence on the cost and cost-effectiveness of TCM for lung cancer. PubMed, Web of Science, and Scopus were searched from inception to July 2025. Eligible studies included economic evaluations comparing TCM with non-TCM treatments or conventional therapies. Outcomes included direct costs, incremental cost-effectiveness ratios (ICERs), and quality-adjusted life years (QALYs).ResultsEight studies met the inclusion criteria, including cohort studies, cross-sectional analyses, and one randomized controlled trial. The included studies spanned from 2003 to 2024, with data primarily from Taiwan and China. Findings were mixed: some studies reported higher total costs for TCM users due to additive, rather than substitutive use alongside conventional therapies. However, several studies demonstrated favorable ICERs for TCM, especially when administered over longer durations. One study showed an ICER of NT880,908 per life-year gained, well below Taiwan’s willingness-to-pay threshold. Outpatient TCM use was often more cost-effective than inpatient care, and herbal medicine appeared more economical than patent medicine.ConclusionAdjunctive TCM may be cost-effective in lung cancer treatment when integrated thoughtfully within national healthcare systems. Cost outcomes vary by care setting, modality, and region. Future standardized, prospective evaluations are warranted to guide the efficient integration of TCM in oncology.